Women's studies encyclopedia - Tierney, Helen; Greenwood Electronic Media (Firm). (Westport, Conn. Greenwood Electronic Media, 1999)
A multidisciplinary reference on the collective experiences of women. Prepared by 425 scholars from all disciplines, features 701 alphabetically listed entries, coverage of 1,250 historical figures, analysis of women and society and culture throughout history, cross-references, and bibliography.
System requirements: 386 PC or higher; 8MB free RAM (12MB for Windows NT); Windows 3.1x or later or Windows NT 3.51 or later; VGA graphics display; fourteen-inch color monitor; 15MB hard disk space (16MB with Windows NT); CD-ROM drive; mouse.
Keywords: Women -- United States -- Encyclopedias; Women -- Encyclopedias; Feminism -- Encyclopedias